Effect of inter-defect interaction on tensile fatigue behavior of a single-walled carbon nanotube with stone wales defects - Zhou, Z. R. (2014)
A refined molecular life prediction scheme for single-walled carbon nanotubes (SWCNTs), taking into consideration C–C bond rotation and preexisting strain under mechanical loads, is proposed. The time-dependent fracture behavior of 12 different cases of zigzag (18,0) SWCNT, each embedded with either a single Stone–Wales (SW) defect of different types or two interacting or noninteracting defects, is studied under axially applied tensile load. It is shown that the patterns of atomistic crack propagation and fatigue lives of SWCNTs are influenced by the type and orientation of the SW defect(s), inter-defect distance, as well as the magnitude of externally applied stress. For SWCNTs with two SW defects, if the inter-defect distance is within the so called indifference length, defect-defect interaction does exist, and it has pronounced effects on diminishing the lives of the nanotubes. Also, the defect-defect interaction is stronger at shorter inter-defect distance, resulting in shorter fatigue lives.